2005
DOI: 10.1007/s00049-005-0323-7
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic induced responses to cabbage root fly larvae (Delia radicum) in Brassica nigra and B. oleracea

Abstract: Feeding by belowground herbivores may induce systemic changes in shoot defence levels that affect the performance of above ground herbivores and higher trophic levels. In this paper two wild Brassica species, B. nigra and B. oleracea were experimentally infested with 10 larvae of the cabbage root fly, Delia radicum. Plant dry masses and glucosinolate levels in shoots, main roots, and fine roots were determined at 3, 7, 12 and 14 days after infestation and compared to those of control plants.The systemic respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 43 publications
3
33
1
Order By: Relevance
“…Furthermore, aliphatic and aromatic glucosinolates sometimes even decline after herbivory (Birch et al 1992;Gols et al 2008;Hopkins et al 1998;Koritsas et al 1989Koritsas et al , 1991Müller and Sieling 2006;van Dam and Raaijmakers 2006), a behavior almost never reported for indolic glucosinolates.…”
Section: Variation By Glucosinolate Typementioning
confidence: 92%
“…Furthermore, aliphatic and aromatic glucosinolates sometimes even decline after herbivory (Birch et al 1992;Gols et al 2008;Hopkins et al 1998;Koritsas et al 1989Koritsas et al , 1991Müller and Sieling 2006;van Dam and Raaijmakers 2006), a behavior almost never reported for indolic glucosinolates.…”
Section: Variation By Glucosinolate Typementioning
confidence: 92%
“…An earlier study on the growth of the generalist herbivore Mamestra brassicae that fed on JA-treated B. oleracea plants revealed that M. brassicae caterpillars performed worst on shoot-induced plants, but unlike P. rapae caterpillars also perform worse on root-induced plants than on control plants (van Dam and Oomen 2008). This indicates the CoQAs could not (fully) explain the performance differences between M. brassicae feeding on differently treated plants.…”
Section: Shoot Induction Leads To An Increase In Levels Of the Metabomentioning
confidence: 95%
“…Even though the increases in JA levels after herbivory may be transient (Schittko et al 2000), they may result in long-lasting chemical changes in the plant, that may last from days to weeks and even years (Agrawal et al 1999;Karban and Baldwin 1997). Moreover, many induced responses are not only localized at the damage site, but expressed in other undamaged plant parts, referred to as the systemic plant response Martin and Muller 2007;Soler et al 2005;Soler et al 2007;van Dam and Oomen 2008;van Dam and Raaijmakers 2006). As induced responses may also be present for long periods of time they may affect not only current, but also successive herbivores and herbivores feeding on plant parts that were not damaged before (Bodnaryk 1994;Broeckling et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations